Attitudes towards Futile Treatments, Moral Distress and Intention to Leave Job in Nurses - Kasim, D. S.; Oflaz, F. (CAMBRIDGE UNIV PRESS, 2023)
31st European Congress of Psychiatry, Paris, FRANCE, MAR 25-28, 2023